Pondok Pesantren Waria Al-Fatah Yogyakarta : Harapan di Tengah Ketidakadilan Hukum dan Sosial - Aryaputri, Aqila Shafiqa; Lewoleba, Kayus Kayowuan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This paper examines the vital role of Pondok Pesantren Waria Al-Fatah Yogyakarta in strengthening human rights protection for the waria community. By examining the legal system in Indonesia and the contributions of the pesantren, this brief discusses how the institution has participated in providing a safe and supportive environment, providing religious education, training skills, and providing legal assistance to members of the transgender community. Through these efforts, Pondok Pesantren Waria Al-Fatah Yogyakarta serves not only as a physical sanctuary, but also as an agent of social change that promotes inclusion and recognition of human rights for all individuals, including waria. Overall, this pesantren serves as an important example of how commitment and concrete efforts can have a positive impact in fighting for the rights of waria and encouraging a more inclusive society.